Mixed facial reanimation technique to treat paralysis in medium-term cases. Issue 5 (May 2018) - Biglioli, Federico; Bolognesi, Federico; Allevi, Fabiana; Rabbiosi, Dimitri; Cupello, Silvia; Previtera, Antonino; Lozza, Alessandro; Battista, Valeria M.A.; Marchetti, Claudio
Abstract: Recent facial paralyses, in which fibrillations of the mimetic muscles are still detectable by electromyography (EMG), allow facial reanimation based on giving new neural stimuli to musculature. However, if more time has elapsed, mimetic muscles can undergo irreversible atrophy, and providing a new neural stimulus is simply not effective. In these cases function is provided by transferring free flaps into the face or transposing masticatory muscles to reinstitute major movements, such as eyelid closure and smiling. In a small number of cases, patients affected by paralysis are referred late — more than 18 months after onset. In these cases, reinnervating the musculature carries a high risk of failure because some or all of the mimetic muscles may atrophy irreversibly while axonal ingrowth is taking place. A mixed reanimation technique to address this involves a neurorrhaphy between the masseteric nerve and a facial nerve branch for the orbicularis oculi, to ensure a stronger innervation to that muscle, associated with the transposition of the temporalis muscle to the nasiolabial sulcus. This gives good symmetry in the rest of the midface, while smiling movement is achievable, but not guaranteed. This one-time facial reanimation is particularly indicated for those who refuse major free-flap surgery or when that may be risky, as in previously operated and irradiated fields. More extensive procedures based on utilizing a free flap to recover smiling, while adding a cross-face nerve graft to restore blinking, may be proposed for motivated patients. Between 2010 and 2015, five patients affected by complete unilateral facial palsy underwent this technique in the Maxillofacial Surgery Department, San Paolo Hospital (Milan, Italy). Symmetry of the middle-third of the face at rest and recovery of smiling was quite good. Complete voluntary eyelid closure was obtained in all cases. Combining temporalis flap rotation and a masseteric-to-orbicularis-oculi-facial-nerve branch neurorrhaphy seems to be a valid solution for those medium-term referred patients.